Pengembangan Web Pemesanan Tiket pada Perusahaan Startup Skilldemy - Reynaldo Fang; Jefri Junifer Pangaribuan (Yayasan Literasi Sains Indonesia, 2022)
Advances in technology like this are something that cannot be avoided in everday life because this happens in tandem with advances in the development of science. The web is a service that makes it easier for users to interact with other users and browse information from the internet. Skilldemy is a startup company fromt the city of Medan, which is engaged in education. Before seminars or workshops are held, instructors or students must first carry out an online-based administrative process via Messages from Instagram, while instructor who want to share their knowledge through seminars or workshops can coordinate via Messages from Whatsapp to discuss what materials will be brought. Because of these problems, it is necessary to build an online seminar or workshop ticket booking website to meet user needs in terms of ticket reservations. The result showed that the design of this website-based ticket booking system made it easier for the participants with the features provided in terms of information and ticket reservations.